MANAJEMEN KEPEMIMPINAN KEPALA SD NEGRI 1 BAKUNG ILIR KECAMATAN GEDUNG MENENG KABUPATEN TULANG BAWANG - Herliyana, Herliyana (UNISAN JURNAL, 2024)
This study aims to determine the leadership management of the head of SDN 1 Bakung ilir. This study uses a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used is observation, interview and documentation techniques. This participatory observation technique was carried out to observe the geographical location in the form of a location plan and environmental conditions, vision, mission, strategy and motto of the head of SDN 1 Bakung ilir. The leadership of the head of SDN 1 Bakung ilir in making a decision for the head of the madrasa is not only unilateral, but considering the size of the effect resulting from the decision, the head of the madrasa as a leader, what stands out from the leadership of the head of SDN 1 Bakung ilir is in communication skills and responsibility.